MONETARY POLICY, FINANCIAL CONSTRAINTS, AND REDISTRIBUTION - Christian Loenser; Andreas Schabert (International Economic Review, 2020)
This article examines how financial constraints affect redistribution via monetary policy. We explore a novel mechanism of monetary nonneutrality, which is based on debt limits imposed in nominal terms. Specifically, when debt is constrained by current income, monetary policy can alter the real terms of borrowing. Changes in inflation exert ambiguous effects, depending on the initial debt/wealth position and the willingness to borrow. We show analytically that borrowers can benefit from increased debt limits under lower inflation rates. This novel effect can dominate conventional debt deflation effects. We find that particularly less indebted borrowers as well as potential future borrowers gain and that aggregate welfare can be enhanced under a permanent reduction in~inflation.
Keywords: 330